Acral melanoma of the extremities_a study of 33 cases Sarawakian patients - Zainal, A.I; Zulkarnaen, M.; Norlida, D.K; Syed Alwi, S.A.R (Medical Journal of Malaysia, 2012)
cral melanoma involve the non-pigmented palmoplantar and subungual areas and are commonly seen among Asians. Patients commonly display advanced stage of disease at presentation. It may appear unnoticed and mimic benign lesions. Methods: Data for this retrospective study was retrieved from Histopathology Unit, Sarawak General Hospital, Malaysia archive from 2003 to 2009. Result: 62.3% cases of malignant melanoma were acral melanoma. The mean age of diagnosis was 64.3±12.1. The involved sites were the heel (39.4%), middle and frontal plantar area (24.2%), toe (24.2%) and web spaces (9.1%). The clinical presentations were; an enlarging mass (60.6%), nonhealing ulcer (24.2%) and abnormal pigmented lesion (15.2%). Most cases exhibited Breslow thickness >4.00 mm (87.9%) and Clark’s levels V (50%). The majority showed moderate (non brisk) tumour infiltrating lymphocytes (57.6%). Ulceration (84.8%) and lymphovascular involvement were seen (24.2%). Conclusion: Acral melanoma is the commonest malignant melanoma in this Sarawakian cohort. Most of the cases presented with advanced stage disease.